Making sense of change and stability in looked after children’s care placements using state sequence analysis - Matthews, Ben; Playford, Chris; McGhee, Janice; Mitchell, Fiona; Dibben, Chris (International Journal of Population Data Science, 2018)
Background Local authorities in Scotland have a responsibility to provide support for vulnerable children and young people, known as ‘looked after children’. This support can include providing care for these children away from home, but there have been growing concerns that children with out of home placements may experience multiple placements before a stable home environment is established for them. As a result, policy changes have aimed to reduce the amount of instability which looked after children experience, but our current understanding of care placement stability in Scotland, and how this has changed over time, is limited. Objectives This project aims to develop our understanding of the patterns of instability experienced by children looked after away from home by applying state sequence analysis (SSA) administrative data regarding children’s care placements from 2008 to 2017 ( 70,000 children). Data are provided by Scottish Government. Methods and Findings SSA is a method commonly used to describe developmental processes which consist of changes between different states - in this case, types of care placement - and provides a number of tools to describe in/stability in these processes. In this paper we use SSA to analyse sequences of placements for multiple cohorts of children to give a detailed description of how placement stability for looked after children in Scotland has changed over the last decade, with results show differences in the typical placement sequence patterns for children of different ages. We and also discuss some methodological challenges which arise when implementing SSA using administrative data. Conclusions Combining SSA and administrative data provides a useful way to describe the typical patterns of looked after care placements, and how these patterns have changed over time.